A AIR BACTERIA INDENTIFICATION BY USING GRAM STAINING: IDENTIFIKASI BAKTERI UDARA MENGGUNAKAN TEKNIK PEWARNAAN GRAM - widia rahmatullah (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2021)
Blood processing is process in bloog service conducted in blood component room and it is possible that blood product get contamination. This research aimed at identifing the gram positive and gram negatifve bacteria which grow on culture medium Nutrient Agar (NA) and Mac Concay Agar (MCA). The research wa true experiment with post test only design whose result were descriptive. The sample of the research wa NA dan MCA media placed in 5 points at the blood component room of UDD PMI Yogyakarta bu using setting plate technique. It was found out that all the 10 petri dishes used as sample contained contamination in medium Nutrient Agar (NA) with result 20 % contained gram positve bacteria in the form of bacillus, 70 % contained gram positive bacteria in the form of coccus, 10 % contained gram positve bacteria in the form of bacillus and coccus, while 10 petri dishes used as sample containde contamination in medium Mac Concay Agar (NA) with result 60% contained gram negative bacteria in the form of bacillus, 30 % contained gram negative bacteria in the form of coccus, and 10 % contained gram negative bacteria in the form of bacillus and coccus.